Methods to determine the biological composition of particulate matter collected from outdoor air - Womiloju, Taiwo O.; Miller, J.David; Mayer, Paul M.; Brook, Jeffrey R. (Atmospheric environment (1994), 2003)
Associations between increased morbidity and exposure to ambient air particulates have been the subject of intense study. Few data exist on the presence of cells or cell materials of fungi, bacteria and pollen in fine particle samples (< 2.5 μm). Because it is not possible to recognize such fragments by conventional means, one approach is to determine the presence of signature biochemicals. This paper reports the development of a method for the analysis of intact glycerophospholipids present in extracts of fungi and pollen common in outdoor air by normal-phase liquid chromatography/electrospray ionization tandem mass spectrometry. Using cluster analysis of the phospholipids found, both mycelia and spores of fungi and pollen common in outdoor air could be separated. Little variation was detected between single spore isolates of individual strains of such fungi isolated across North America. White Birch and ragweed pollen contained similar phospholipid patterns but different from the fungi. From literature data, both were different than Gram negative bacteria. Semi-hivolume fine particle samples were collected on glass fibre filters in three locations in and near Toronto, extracted and analyzed. The concentrations of phospholipids measured suggested that fungal cells and pollen were responsible for 12–22% of the organic carbon fraction or 4–11% of the total mass depending upon location. The qualitative and quantitative estimates obtained compared favourably to data from concurrent rotorod samples. This suggests that, with improved sensitivity, the analysis of a larger number of samples would provide useful data for epidemiological studies and on the nature of organic carbon in fine particulate samples.